Development of Bus and Line Control Method for Short-Circuit Current Reduction Using Genetic Programming - Dabin Son; Sangwook Han (Energies, 2022)
In this study, genetic programming (GP) is used for optimizing bus and line separation methods to reduce the short-circuit current. Expanding power systems led to intensive electric power and more transmission lines, reducing the grid impedance. This increases the short-circuit currents that occur during failure, and it is impossible to continue developing higher-capacity breakers to accommodate such short-circuit currents. Therefore, the short-circuit currents must be managed systematically through busbar separation and line separation. However, there are countless possible bus and line separation schemes for power systems. Furthermore, to comply with power-system reliability standards, no lines or transformers should be overloaded after such controls are applied. This paper proposes the use of GP to optimize the bus and line separation methods for obtaining a solution. The solutions are limited to methods that can be implemented in real power systems, reducing the convergence probability and optimization time. The proposed technique is useful for designing power systems with consideration of the short-circuit current.